Is it time to consider a different way of swimming backstroke? - Maglischo, E. W. (Journal of Swimming Research, 2014)
For several years many of the world's best backstroke swimmers, both male and female, have been performing this stroke in a unique style which may be superior to the traditional way that backstroke has been taught. This paper will describe the various ways this unique style of backstroke is being swum and its possible benefits.